Improvement of front car bumper system - Muhamad Firdaus, Mahmud (2008)
Designing the bumper with the focus on an improvement aspect is very important in the automotive industry. The goals are to increase the performance of the bumper and also to find the solution to reduce the cost of the bumper hence able to reduce the production cost. The costs of the bumper is high because of the amount of material used and it also involves many processes including making the grille at the center of bumper. The new design considers on reducing the amount of material use and also eliminating the process involve in manufacture the bumper for example eliminating the grille attachment. The new design also must improve the ability to absorb more impact load and increase the protection of the front car component. This project intention is to design an improved of front car bumper and to find the solution for the problem of high cost and the replacing cost for the front bumper and lastly emphasizing the cost reducing aspect. The method have been employed was study the front bumper system, design and analyze the alternative front bumper using CAD software. The suitable material that can be used as the bumper in terms of economical but still maintaining the toughness is Plastic-Polycarbonate (Molded) which is not expensive compare to the best material from the analysis E-Glass Fiber, Plastic-Nylon Type 6/6 and Plastic ABS (Molded). The suitable material to be use for making beam is AISI E 52100 Steel. Rearrangement of the mounting positions gives a different effect on the ability to withstand the impact force. Additional plate in the improvement design proved increasing the toughness of the beam.